Du Sud à la Caraïbe : La Nouvelle-Orléans, ville créole - Nathalie DESSENS (E-REA)
This article examines the historiography of New Orleans, showing how the evolution of perspectives has enabled a progressive “recentering” of the city. Long perceived as a “misfit” city within the United States and even within the American South, the city has been progressively “recentered” in the history of the young American republic and in the Atlantic space in the past twenty years. A decentering of the perspective has thus enabled to no longer consider the Crescent City as marginal in North-American history. The article proposes to use the new paradigm of the Greater Caribbean, tangential and complementary to the Atlantic space defined by Bernard Bailyn in the 1980s, to complete the recentering of 19th-century New Orleans.